Acute effects of the translocator protein drug ligand FGIN-1-27 on serum testosterone and luteinizing hormone levels in male Sprague-Dawley rats†. Issue 3 (18th October 2018) - Chen, Fenfen; Lu, Hemin; Chen, Panpan; Zhao, Xingxing; Guan, Xiaojui; Liang, Qingquan; Zirkin, Barry R; Ye, Leping; Chen, Haolin
Abstract: We reported that FGIN-1-27 (N, N-dihexyl-2-(4-fluorophenyl)indole-3-acetamide, FGIN), a synthetic ligand for translocator protein (TSPO, 18 kDa), increased serum testosterone levels in young and aged Brown Norway rats after its administration daily for 10 days. It is not known, however, how soon after treatment with FGIN serum testosterone rises, how long levels remain elevated after cessation of treatment, or whether the drug acts solely through TSPO. Adult Sprague-Dawley male rats received a single ip dose of FGIN (1 mg/kg BW). Serial blood samples were collected, and serum testosterone and luteinizing hormone (LH) were assessed hourly throughout 24 h. Testosterone concentration was maximal by 3 h, remained significantly higher than the controls at 10 h, and returned to the control level by 24 h. Consistent with the in vivo study, culturing isolated Leydig cells with either FGIN (40 μM) or LH (0.1 ng/ml) resulted in significantly increased testosterone production by 30 min, and the stimulatory effects persisted through 48 h. At a very early (15 min) treatment time, however, FGIN significantly increased testosterone production but LH had not yet done so. Surprisingly, in vivo treatment with FGIN not only increased serum testosterone but also serum LH concentration, raising the possibility that FGIN may increase serum testosterone concentration by dual mechanisms. Abstract : FGIN-1-27, a TSPO drug ligand, can acutely increase serum testosterone concentration by acting directly on the Leydig cells and indirectly through luteinizing hormone.